Mechanism of Nanocomposite Formation in the Layer-by-Layer Single-Step Electropolymerization of π-Conjugated Azopolymers and Reduced Graphene Oxide: An Electrochemical Impedance Spectroscopy Study - Olean-Oliveira, André [UNESP]; Oliveira Brito, Gilberto A.; Teixeira, Marcos F. S. [UNESP] (American Chemical Society (ACS), 2020)
This work presents a study of the formation mechanism of electrochemically deposited alternating layers of azopolymer and graphene oxide, as well as a systematic study of the physicochemical characteristics of the resulting nanocomposite films by electrochemical impedance spectroscopy. The nanocomposite films were constructed by cyclic electropolymerization, which allowed for the assembly of thin films with alternating azopolymers and reduced graphene oxide (rGO) layers in one step. Morphological characterizations were performed by atomic force microscopy and scanning electron microscopy and verified that the electrodeposition of the poly(azo-BBY) polymeric film occurred during the anodic sweep, and the deposition of graphene oxide sheets took place during the cathodic sweep. By analyzing the electrochemical impedance spectra using equivalent circuit models, variations in the resistance and capacitance values of the system were monitored as a function of the amount of electrodeposited material on the fluorine doped tin oxide electrode. In addition, the interfacial phenomena that occurred during the electroreduction of the rGO sheets were monitored with the same method.